1993
DOI: 10.1111/j.1744-7348.1993.tb04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between two synthetic pyrethroids and the spread of two non‐persistent viruses in cowpea

Abstract: SummaryThe effectiveness of the synthetic pyrethroids deltamethrin and lambda‐cyhal‐othrin in preventing (i) aphid colonisation of four cowpea cultivars with different levels of aphid resistance and (ii) the introduction and subsequent spread of cowpea aphid‐borne mosaic virus and cucumber mosaic virus was investigated under tropical field conditions.Sprays of these pyrethroids eight days apart prevent aphid colonisation and within crop spread of virus by the colonising Aphis craccivora. However, neither delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…It is well established that aphid feeding results in a significant reduction of crop yield worldwide and thus reducing aphid populations through novel mechanisms has been of significant interest. Current aphid control programs rely heavily on the use of neurotoxic insecticides, and although neurotoxic insecticides are a validated approach for reducing aphid populations, it has been shown that some neurotoxic insecticides, such as pyrethroids, stimulate aphid probing and cause aphids to move from plant to plant, ultimately increasing virus spread . This plant‐to‐plant movement and increased probing behavior can increase the spread of nonpersistent plant viruses, thus the identification of molecules that induce mortality through a novel mechanism (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that aphid feeding results in a significant reduction of crop yield worldwide and thus reducing aphid populations through novel mechanisms has been of significant interest. Current aphid control programs rely heavily on the use of neurotoxic insecticides, and although neurotoxic insecticides are a validated approach for reducing aphid populations, it has been shown that some neurotoxic insecticides, such as pyrethroids, stimulate aphid probing and cause aphids to move from plant to plant, ultimately increasing virus spread . This plant‐to‐plant movement and increased probing behavior can increase the spread of nonpersistent plant viruses, thus the identification of molecules that induce mortality through a novel mechanism (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…) and extremely important from an economic perspective, because their rapid transmission strategy makes chemical control of vectors largely ineffective in monocultures of susceptible hosts where insecticides may instead stimulate increased movement and probing by vectors before they are killed (Roberts et al . ; Perring, Gruenhagen & Farrar ). It may also be useful to compare and contrast the effects of insect‐vectored viruses with vertically transmitted or mechanically transmitted viruses that do not rely on insect vectors and thus would not be expected to induce similar changes in plant chemistry (e.g.…”
Section: Future Directionsmentioning
confidence: 99%
“…Heavy infestations cause stunting, delays in flower initiation and, in extreme cases, death of the plant. Furthermore, A. craccivora has been implicated as the main vector of the non-persistent cowpea aphid-borne mosaic virus (Lapido and Allen, 1979;Thottappilly and Rössel, 1985;Atiri et al, 1986;Roberts et al, 1993).…”
Section: Introductionmentioning
confidence: 98%